Analysis of wave dispersion and attenuation effects on seismic low-frequency reflections of a poroelastic layer. Issue 1 (2nd January 2021) - He, Yan-Xiao; Wang, Shangxu; Tang, Genyang; Wu, Xinyu; Xi, Bo
Abstract : We investigated reflection dispersion characteristics of a poroelastic layer with patchy saturations in seismic low-frequency range. Frequency-dependent attenuation and dispersion of phase velocity were determined with varying fluid saturation, porosity, permeability and heterogeneity size, using analytical solutions of a generalised 1D White's model proposed here, obtained by incorporating capillary forces into the patchy saturation model. Numerical predictions were employed in combinations with an approximation for the complex and frequency-dependent reflection coefficient from an attenuating thin layer embedded in a dissipative background medium, so as to give a deep insight into the impacts of velocity dispersion and tuning, as well as acoustic impedance contrast, on the seismic low-frequency reflections. Results from this study suggest that wave-induced fluid flow in poroelastic media might account for low-frequency reflection signature anomalies that are associated with fluid saturation in the pore space. We also observed that seismic reflection coefficients of a partially saturated layer can vary strongly versus frequencies, especially in low-frequency range where high attenuation and dispersion can take place due to fluid partial saturation. Analysis of the crossplots of the magnitude for reflection coefficients and dispersion showed that attenuation, dispersion and tuning are more sensitive to gas saturation, porosity, and heterogeneity size. Thus the crossplot provides a useful means for detecting changes in fluid saturation and rock properties.